2013
DOI: 10.1086/671191
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration Hardly Slows Hopping Toads (Rhinella granulosa) from Xeric and Mesic Environments

Abstract: The locomotor capacity of amphibians depends strongly on temperature and hydration. Understanding the potential interactions between these variables remains an important challenge because temperature and water availability covary strongly in natural environments. We explored the effects of temperature and hydration on the hopping speeds of Rhinella granulosa, a small toad from the semiarid Caatinga and the Atlantic Rain Forest in Brazil. We asked whether thermal and hydric states interact to determine performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 49 publications
2
16
0
1
Order By: Relevance
“…2013; Titon and Gomes, 2010). Our results clearly showed that the better hydrated the animal, the better was their absolute locomotor performance in all temperatures tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2013; Titon and Gomes, 2010). Our results clearly showed that the better hydrated the animal, the better was their absolute locomotor performance in all temperatures tested.…”
Section: Discussionmentioning
confidence: 99%
“…2013 and references therein). Moreover, previous studies found that locomotion may be greatly influenced by temperature (Rome, Stevens, & John‐Alder 1992) and dehydration (Preest & Pough 1989) in amphibians.…”
Section: Methodsmentioning
confidence: 99%
“…Because physiological tolerances to abiotic conditions constrain organismal fitness (Navas, ), it has been suggested that the occurrence of any given species across various environments may be associated with local adaptation (Bridle & Vines, ; Hohenlohe et al, ; Huey, Gilchrist, Carlson, Berrigan, & Serra, ). Yet, experimental studies indicate that physiological function can be highly conserved within species over wide environmental gradients (e.g., Crowley, ; Hertz, Huey, & Nevo, ; John‐Alder, Barnhart, & Bennett, ; Prates & Navas, , Prates, Angilleta, Wilson, Niehaus, & Navas, ; Van Damme, Bauwens, Castilla, & Verheyen, ), and this lack of phenotypic differentiation has been associated with the homogenizing effects of population gene flow (Bridle & Vines, ; Lenormand, ). It is therefore unclear to which extent the occurrence of species in distinct environments is linked to local adaptation and associated genetic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…From this, we can infer that greater osmotic concentrations in surrounding water are physiologically stressful for this species. It is known that dehydration stress (in this study, caused by air or saline media) is an important factor for the increase of frequency or duration of postures associated with water conservation in anurans (Heatwole et al, 1969;Brekke et al, 1991;Hillyard et al, 2007;Pough et al, 1983;Hillyard et al, 1998;Prates et al, 2013;Taylor et al, 1999;Viborg and Rosenkilde, 2001;Tran et al, 1992) Hillyard et al (1998, while studying the physiological processes involved in the behavioral response of Bufo marinus, normally hydrated as well as dehydrated (loss of 10% of initial body mass), and rehydration in NaCl solutions with concentrations of 250 mmol/L and 500 mmol/L, saw that both groups exhibited the "ventral skin down" posture (equivalent to this study's "a" or water conservation posture), but the normally hydrated individuals kept themselves in this posture for a shorter time than individuals which were dehydrated.…”
Section: Discussionmentioning
confidence: 90%